The Thomistic Dissolution of the Logical Problem of Evil - Feser, Edward (Religions, 2021)
In his book ‘Is a Good God Logically Possible?’, James Sterba argues that the existence of much of the evil to be found in the world is logically incompatible with the existence of God. I defend the Thomistic view that when one properly understands the nature of God and of his relationship to the world, this so-called logical problem of evil does not arise. While Sterba has responded to the version of the Thomistic position presented by Brian Davies, I argue that his response fails.